2018
DOI: 10.1002/cbic.201800143
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Turnover Kinetics Reveal a Distinct Mode of Thiamine Diphosphate‐Dependent Catalysis in Vitamin K Biosynthesis

Abstract: MenD, or (1R,2S,5S,6S)-2-succinyl-5-enolpyruvyl-6-hydroxycyclohex-3-ene-1-carboxylate (SEPHCHC) synthase, uses a thiamine diphosphate (ThDP)-dependent tetrahedral Breslow intermediate rather than a canonical enamine for catalysis in the biosynthesis of vitamin K. By real-time monitoring of the cofactor chemical state with circular dichroism spectroscopy, we found that a new post-decarboxylation intermediate was formed from a multistep process that was rate limited by binding of the α-ketoglutarate substrate be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 69 publications
5
18
0
Order By: Relevance
“…106,107 In addition to mostly hydrophobic amino acids contributing to the active site, usually five basic amino acid residues provide a suitable chemical environment to promote 1,4-conjugate addition and stabilisation of the product. 104,105,[107][108][109] The most important residues that contribute to the process are: (i) a highly conserved glutamate activating ThDP, (ii) two conserved arginines that are suggested to be crucial for substrate binding and catalysis, and (iii) two polar amino acids (Gln and Ser) that finally enable product formation (Fig. 4I).…”
Section: Sephchc Synthases Exhibit a Typical Thdp-dependent Enzyme Foldmentioning
confidence: 99%
See 2 more Smart Citations
“…106,107 In addition to mostly hydrophobic amino acids contributing to the active site, usually five basic amino acid residues provide a suitable chemical environment to promote 1,4-conjugate addition and stabilisation of the product. 104,105,[107][108][109] The most important residues that contribute to the process are: (i) a highly conserved glutamate activating ThDP, (ii) two conserved arginines that are suggested to be crucial for substrate binding and catalysis, and (iii) two polar amino acids (Gln and Ser) that finally enable product formation (Fig. 4I).…”
Section: Sephchc Synthases Exhibit a Typical Thdp-dependent Enzyme Foldmentioning
confidence: 99%
“…This is in contrast to other ThDP-dependent enzymes where the enamine form can be detected as well. [102][103][104][105][107][108][109] ThDP and the C2a-decarboxylated 2-oxoglutarate are proposed to be connected in a unique rigid conformation with a defined stereochemistry by two conserved arginine residues keeping…”
Section: Sephchc Synthases Exhibit a Typical Thdp-dependent Enzyme Foldmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 It was suggested that this arose from the transfer of a proton from N4′ of ThDP to the C2α-carbanion form of Int2. 17,23 Scheme 4 shows that such a transfer would produce Int2-Td, that is, the cofactor would be in its N4′ imino (IP) form. We have evaluated this possibility and found the IP form to be ca.…”
Section: Resultsmentioning
confidence: 99%
“…22 This structure was later combined with stopped-flow and mutagenesis experiments to prompt the suggestion that MenD may operate in a novel catalytic mode, one quite distinct from the canonical enamine chemistry. 23 Despite the plethora of X-ray structures, mutagenesis, and kinetic investigations, the MenD reaction mechanism has not been fully established. A number of questions are still open, the most important of which relates to the catalytic competence of the post-decarboxylation tetrahedral species.…”
Section: Introductionmentioning
confidence: 99%